Philosophical Ideas of Arne Næss in the Humanitarian Diplomacy of Norway - M. G. Zubov (Vestnik MGIMO-Universiteta)
Næss A. became in his lifetime the most prominent Norwegian philosopher. Over thirty years of his life he taught at the University of Oslo and approximately the same number of years he devoted to pure science. During his long life as a scientist, he studied various fields of philosophy, however he is mostly known for his research in the field of deep ecology. The scale of his personality and prestige in Norwegian philosophy can only be compared to that of one of the most outstanding figure of Norway in politics - E.Gerhardsen. He united two of his basic interests - philosophy and ecology, and formulated eight principles, which in general terms characterise the notion of «deep ecology». These eight principles, according to philosopher, are based on the concept that every living being has his own value. The author of the arcticle makes it a point to show on separate examples to what extend the ideas of Næss A. are compatible with the basic principles of Norway's contemporary humanitarian diplomacy - humanity, neutrality, impartiality and independence, - as well as with the aims put forward by Norway in this respect which are to encure the needed with the necessery security and assistance; to finance humanitarian actions based on the international principles of humanity, neutrality, impartiality and independence; to prepare international community to responses to global humanitarian challenges of the future; to prevent and respond to humanitarian crises and participate in eleminating their aftermath. Norway - one of the few countries in the world allocating 1 % of their GNP for the aims of the UN Millennium Programme - works actively in such directions of humanitarian diplomacy as combating climate change, protecting the environment, facilitating international cooperation in the field of development, peace-building and humanitarian assistance. Having assessed the potential ofapplicability of the principles of deep ecology in practical implementation of the humanitarian diplomacy of Norway, the author also tries to explain concisely by what material means such diplomacy is procured.